Racial, Ethnic, and Language-Based Inequities in Inpatient Opioid Prescribing by Diagnosis from Internal Medicine Services, a Retrospective Cohort Study - Mihir Joshi; Priya A. Prasad; Colin C. Hubbard; Nicholas Iverson; Solmaz P. Manuel; Margaret C. Fang; Aksharananda Rambachan (Pain Research and Management)
Introduction. Opioid administration is extremely common in the inpatient setting, yet we do not know how the administration of opioids varies across different medical conditions and patient characteristics on internal medicine services. Our goal was to assess racial, ethnic, and language-based inequities in opioid prescribing practices for patients admitted to internal medicine services. Methods. We conducted a retrospective cohort study of all adult patients admitted to internal medicine services from 2013 to 2021 and identified subcohorts of patients treated for the six most frequent primary hospital conditions (pneumonia, sepsis, cellulitis, gastrointestinal bleed, pyelonephritis/urinary tract infection, and respiratory disease) and three select conditions typically associated with pain (abdominal pain, acute back pain, and pancreatitis). We conducted a negative binomial regression analysis to determine how average administered daily opioids, measured as morphine milligram equivalents (MMEs), were associated with race, ethnicity, and language, while adjusting for additional patient demographics, hospitalization characteristics, medical comorbidities, prior opioid therapy, and substance use disorders. Results. The study cohort included 61,831 patient hospitalizations. In adjusted models, we found that patients with limited English proficiency received significantly fewer opioids (66 MMEs, 95% CI: 52, 80) compared to English-speaking patients (101 MMEs, 95% CI: 91, 111). Asian (59 MMEs, 95% CI: 51, 66), Latinx (89 MMEs, 95% CI: 79, 100), and multi-race/ethnicity patients (81 MMEs, 95% CI: 65, 97) received significantly fewer opioids compared to white patients (103 MMEs, 95% CI: 94, 112). American Indian/Alaska Native (227 MMEs, 95% CI: 110, 344) patients received significantly more opioids. Significant inequities were also identified across race, ethnicity, and language groups when analyses were conducted within the subcohorts. Most notably, Asian and Latinx patients received significantly fewer MMEs and American Indian/Alaska Native patients received significantly more MMEs compared to white patients for the top six most frequent conditions. Most patients from minority groups also received fewer MMEs compared to white patients for three select pain conditions. Discussion. There are notable inequities in opioid prescribing based on patient race, ethnicity, and language status for those admitted to inpatient internal medicine services across all conditions and in the subcohorts of the six most frequent hospital conditions and three pain-associated conditions. This represents an institutional and societal opportunity for quality improvement initiatives to promote equitable pain management.